IMPLEMENTATION OF LEARNING USING BLENDED LEARNING BASED INDEPENDENT CURRICULUM - Daulat Marulitua Tambunan; Aleksky BMB; Ita Marlina; Yuliana Gunawan (INJOSEDU: International Journal of Social and Education, 2025)
The discussion of this article begins with an emphasis on the importance of quality human resources, which can be produced through the development of educational curriculum. The differences between the 2013 Curriculum and the Merdeka Curriculum, such as the emphasis on developing Pancasila student character, gradual learning outcomes, and teacher flexibility, are explained as innovations that encourage more innovative learning. Driving schools are an important element in the transformation of character education, focusing on literacy, numeracy and student character. This program targets student learning outcomes holistically and embodies the Pancasila student profile. In facing the pandemic, the implementation of the Merdeka Curriculum in driving schools uses a blended learning model, which combines face-to-face and distance learning. The research method uses literature study, with data analysis, especially related to planning in the Independent Curriculum teaching module. It is hoped that the research results can provide input for improving learning tools and processes for schools that will implement the Independent Curriculum. The article also discusses curriculum development, the 2013 Curriculum policy Revision to the Independent Curriculum, as well as the objectives and advantages of the Independent Curriculum. The conclusions from this discussion include a focus on character development, curriculum flexibility, the role of driving schools, and adapting the blended learning model. It is hoped that this article will make a positive contribution in supporting the implementation of the Independent Curriculum in Indonesia.